Study Of Physico-Chemical Properties Of Kasura Dam From Jalna District (M.S) India (Global Journal of Science Frontier Research, 2012)
The present study deals with the physical and chemical properties of the water of Kasura dam is located in Marathwada region (M.S) India. Determination of physico-chemical parameter (Atmospheric Temp, Water. Temp, Rain fal , Ca ,Cl, CO2, DO) were carried out to indentify the nature and quality of the water of Kasura dam year (July 2008-June 2009). Kasura dam is situated 19 km away from South side of Partur city. It lies between 190.30'0'' North latitude, 760.15'50'' East longitude and altitude. The details of results are discussed in the text.
Keywords: Physico chemical; Kasura; Marathwada; AtTemp; WtTemp